Efficacy Comparison of Different Acupuncture Treatments for Primary Insomnia: A Bayesian Analysis. (3rd September 2019) - Xu, Huachong; Shi, Yucong; Xiao, Yike; Liu, Pei; Wu, Sizhi; Pang, Peng; Deng, Li; Chen, Xiaoyin
Abstract : Background . Acupuncture treatments are used frequently in the treatment of primary insomnia considering its less side effect. However, most treatment choices are made just based on personal experience among different forms of acupuncture. This study compared the effectiveness of different forms of acupuncture for primary insomnia by using network meta-analysis. Methods . All randomized controlled trials (RCTs) of acupuncture treatments for primary insomnia were searched in seven databases from the date of database inception to January 6, 2019, including PubMed, Web of Science, Embase, Cochrane Library, Wanfang database, China National Knowledge Infrastructure (CNKI) database, and VIP Chinese Science and Technique Journals (CQVIP) database. After screening, the effectiveness rate was extracted from the included RCTs as primary outcomes. The network meta-analysis was performed by Review Manager 5.3, Stata13.0, and GeMTC 0.14.3. Results . Forty-two studies were included, which contained 3304 participants among 6 interventions. Based on the ranking probability and compared to western medicine, scalp acupuncture (OR = 8.12, 95% CI (4.07, 16.81)) is considered to be the most effective method, followed by electroacupuncture (OR = 6.29, 95% CI (3.36, 12.67)), electroacupuncture combined scalp acupuncture (OR = 5.20, 95% CI (2.43, 11.28)), warm acupuncture (OR = 3.79, 95% CI (1.85, 8.16)), and conventional acupuncture (OR = 2.86, 95% CI (2.05, 3.95)). There was no significant difference between the results of direct and indirect comparisons. Conclusions . The finding indicated that five acupuncture methods may be all effective in the treatment of primary insomnia, and scalp acupuncture seems to be the best treatment. However, the overall quality of the included trials could only be ranked as medium to low quality, and higher quality RCTs are warranted for sufficient evidence.